The Role of Interventional Endoscopic Ultrasound in Liver Diseases: What Have We Learnt? - Cosmas Rinaldi A. Lesmana; Maria Satya Paramitha; Rino A. Gani (Canadian Journal of Gastroenterology and Hepatology)
Chronic liver disease (CLD) is still a major problem, where the disease progression will lead to liver cirrhosis (LC) or hepatocellular carcinoma (HCC). Portal hypertension (PH) management and loco-regional therapy for HCC have become the cornerstones in advanced liver disease management. Recently, there are studies looking at the potential role of interventional endoscopic ultrasound (EUS) in liver diseases. EUS may be useful in vascular changes of the digestive wall evaluation, performing dynamic assessment of hemodynamic changes, predicting variceal bleeding and rebleeding risk, and assessing the pharmacological effects. In PH management, EUS-guided vascular therapy—which revolves around glue injection, endovascular coil placement/embolization, and combination of both—has shown promising results. As a diagnostic modality for liver cancer, the implementation of EUS in liver diseases is currently not only limited to liver biopsy (EUS-LB) but also in shear-wave elastography (SWE) and portal pressure gradient measurement, as well as portal vein sampling. The application of EUS-guided radiofrequency ablation (EUS-RFA) and tumor injection can also overcome the limitations shown by both modalities without EUS. Nevertheless, establishing EUS as a firm diagnostic and therapeutic modality is still challenging since the performance of interventional EUS requires high expertise and adequate facilities.